(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Several complex-compounds based on derivatives of 3-(2-hydroxyphenyl)-1,2,4-triazole were synthesized. Obtained compounds were studied by means of NMR-spectroscopy. The structure of synthesized complexes were offered according to the results